Customer loyalty toward internet banking in Nigeria - Ogiri, Ibrahim Aishatu (2014)
The increasing usage of internet banking service among Nigerians has made competition fiercer among internet banking providers. This is as a result of easy accessibility of information about banking activities which enable the customer to easily compare various banks product and thereby easily deflecting from one bank to another, resulting in diminishing customer loyalty. This results in retail banks continually working hard to make new innovations or improve their internet banking services in order to make their bank a better choice for customer as well as to retain them. Customer loyalty has been identified by researcher as an important yardstick for the survival and profitability of e-commerce. The purpose of this study is to investigate the influence of trust, satisfaction, reputation, commitment and website quality on customer e-loyalty, to identify the most essential factor influencing customer e-loyalty and to investigate the impact of gender, age, education and technophobia as moderators on the relationship between the dependent variable and the independent variables. Two hundred questionnaires were distributed to the sample population. One hundred sixty nine questionnaires were used for the data analysis. Multiple regressions analysis was used to analyse the data. The results of the study revealed that reputation, satisfaction, trust and commitment have a positive influence on customer e-loyalty towards internet banking. However, multiple regression results showed that website quality has an insignificant influence on customer e-loyalty towards internet banking. The result further showed that reputation is most essential in building customer e-loyalty followed by satisfaction, trust and commitment.